Regional distributions of UDP-glucuronosyltransferase activities toward estradiol and serotonin in the liver and small intestine of cynomolgus macaques. Issue 4 (August 2020) - Nakanishi, Yasuharu; Uno, Yasuhiro; Yamazaki, Hiroshi
Abstract: The cynomolgus macaque is a nonhuman primate species that is often used in drug metabolism studies during drug development. However, the localization of UDP-glucuronosyltransferases (UGTs), essential drug-metabolizing enzymes, has not been fully investigated in the liver and small intestine of cynomolgus macaques. In this study, UGT activities were analyzed in liver (five lobes) and small intestine (the duodenum and six sections from the proximal jejunum to the distal ileum) using typical probe substrates of human UGTs: 7-hydroxycoumarin, estradiol, serotonin, propofol, and zidovudine. In liver, UGT activities with respect to all substrates were detected, and the activity levels were similar in all liver lobes of the cynomolgus macaques tested. In contrast, in the small intestine, UGT activities toward all substrates were detected, but their levels generally decreased from jejunum to ileum in cynomolgus macaques. The localization of estradiol 3- O -glucuronosyltransferases and serotonin O -glucuronosyltransferases (which are mainly UGT1A enzymes) appear to be different in liver and small intestine. These results collectively suggest that, in cynomolgus macaques, UGT1As are differentially localized in the small intestine but are relatively homogeneously distributed in the liver. Graphical abstract: Image 1